Approaches by the US National Institutes of Health to support rigorous scientific research on dietary supplements and natural products. Issue 3 (14th January 2016) - Kuszak, A. J.; Hopp, D. C.; Williamson, J. S.; Betz, J. M.; Sorkin, B. C.
Abstract : Mechanistic, clinical, and epidemiological research relevant to dietary supplements (DS) is supported by the U.S. National Institutes of Health. The Office of Dietary Supplements and the National Center for Complementary and Integrative Health promote the development and appropriate use of rigorous and comprehensive DS analyses which are critical for research reproducibility, particularly when the investigational DS include chemically complex natural products with unclear mechanisms of action.